Phase-engineered high-entropy metastable FCC Cu2−yAgy(InxSn1−x)Se2S nanomaterials with high thermoelectric performance. Issue 35 (24th August 2022) - Zhang, Wanjia; Lou, Yue; Dong, Hongliang; Wu, Fanshi; Tiwari, Janak; Shi, Zhan; Feng, Tianli; Pantelides, Sokrates T.; Xu, Biao
Abstract : The retention in size caused by the residual ligands drives the stability of metastable phase, enhancing structure symmetry and leading to good electrical transport. The distorted lattice and multidimensional defects intensify phonon scattering. Abstract : Crystal-phase engineering to create metastable polymorphs is an effective and powerful way to modulate the physicochemical properties and functions of semiconductor materials, but it has been rarely explored in thermoelectrics due to concerns over thermal stability. Herein, we develop a combined colloidal synthesis and sintering route to prepare nanostructured solids through ligand retention. Nano-scale control over the unconventional cubic-phase is realized in a high-entropy Cu2− y Ag y (In x Sn1− x )Se2 S ( x = 0–0.25, y = 0, 0.07, 0.13) system by surface-ligand protection and size-driven phase stabilization. Different from the common monoclinic phase, the unconventional cubic-phase samples can optimize electrical and thermal properties through phase and entropy design. A high power factor (0.44 mW m −1 K −2 ), an ultralow thermal conductivity (0.25 W m −1 K −1 ) and a ZT value of 1.52 are achieved at 873 K for the cubic Cu1.87 Ag0.13 (In0.06 Sn0.94 )Se2 S nanostructured sample. This study highlights a new method for the synthesis of metastable phase high-entropy materials and gives insights into stabilizing the metastable phase through ligand retention in other research communities.